Investigation of probe surfaces after ion cyclotron wall conditioning in ASDEX upgrade. (August 2017) - Garcia-Carrasco, A.; Petersson, P.; Schwarz-Selinger, T.; Wauters, T.; Douai, D.; Bobkov, V.; Cavazzana, R.; Krieger, K.; Lyssoivan, A.; Möller, S.; Spolaore, M.; Rohde, V.; et al.
Highlights: Probe surfaces have been analysed after ICWC operation on in a metal-wall fusion machine. The concentration ratio He/C+B was 0.7. D, He, B, C, N, O was detected on originally clean tungsten probes. Abstract: For the first time, material analysis techniques have been applied to study the effect of ion cyclotron wall conditioning (ICWC) on probe surfaces in a metal-wall machine. ICWC is a technique envisaged to contribute to the removal of fuel and impurities from the first wall of ITER. The objective of this work was to assess impurity migration under ICWC operation. Tungsten probes were exposed in ASDEX Upgrade to discharges in helium. After wall conditioning, the probes were covered with a co-deposited layer containing D, B, C, N, O and relatively high amount of He. The concentration ratio He/C+B was 0.7. The formation of the co-deposited layer indicates that a fraction of the impurities desorbed from the wall under ICWC operation are transported by plasma and deposited away from their original location.